Heritage of waqf properties in Türkiye: exploring tour guides' roles in spreading waqf appreciation among tourists - Mohd Ali, Siti Nadiah; Arshad, Huraizah; Fauzi, Nurul Sahida; Atan, Nur Atika; Abdullah, Lizawati (Universiti Teknologi MARA, Perak, 2025)
This qualitative research study looks into tour guides' important role in disseminating waqf knowledge to tourists visiting Türkiye. Waqfs, which are embedded in Türkiye’s historical and cultural landscape, represent an important aspect of Islamic heritage dating back to the Ottoman Turkish Empire and include institutions such as mosques, madrasahs, and charitable foundations. Despite its historical significance, waqf property in Türkiye remains the primary attraction for tourists visiting the country. As a result, the purpose of this study is to explore the role of tour guides who lead tours to Türkiye, with a focus on the significance of waqf among tourists. Based on this qualitative research approach, an observation method was used by a Turkish tour guide who led a tour of 30 Malaysian tourist groups from February 28 to March 8, 2024. Observations were made of the tour guide's explanations and speeches when dealing with Malaysian tourists. Thematic analysis was used to find recurring patterns, themes, and narratives in the collected data. The findings revealed that the tourist guide's focus is not on waqf properties specifically. The explanation provided fails to define the role of waqf in shaping the development of Türkiye since the Ottoman Caliphate's reign. In fact, the tourist guide focuses heavily on Turkiye's history after and before the fall of the Ottoman Empire. The study's findings are expected to contribute to the existing literature on the importance of tourism waqf heritage, particularly in Türkiye and other countries around the world, in order to establish waqf as a tourism tool that must be preserved and its role introduced to those who visit countries with waqf assets. Tourism stakeholders, particularly policymakers, should incorporate waqf heritage into tourism narratives and encourage responsible tourism practices in order to respect and preserve waqf cultural heritage in Türkiye and neighbouring countries.